2020
DOI: 10.1093/molbev/msaa027
|View full text |Cite
|
Sign up to set email alerts
|

Cis- and Trans-Regulatory Variations in the Domestication of the Chili Pepper Fruit

Abstract: The process of domestication requires the rapid transformation of the wild morphology into the cultivated forms that humans select for. This process often takes place through changes in the regulation of genes, yet, there is no definite pattern on the role of cis- and trans-acting regulatory variations in the domestication of the fruit among crops. Using allele-specific expression and network analyses, we characterized the regulatory patterns and the inheritance of gene expression in wild and cultivated access… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 60 publications
4
17
0
Order By: Relevance
“…This percentage can be considered to be high, given the dissimilarities of the above-mentioned factors (plots and results available upon request). On the other hand, Díaz-Valenzuela et al [ 41 ] reported results from the analyses of one cultivated accession, one wild accession, and their only at 40 DAA. Given that this study does not include gene expression measurements at different times of fruit development, it is impossible to examine their findings in the framework of our work.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This percentage can be considered to be high, given the dissimilarities of the above-mentioned factors (plots and results available upon request). On the other hand, Díaz-Valenzuela et al [ 41 ] reported results from the analyses of one cultivated accession, one wild accession, and their only at 40 DAA. Given that this study does not include gene expression measurements at different times of fruit development, it is impossible to examine their findings in the framework of our work.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the authors of [ 36 ] provided insights in order to evaluate the adaptive landscape of cultivated peppers [ 40 ] and reported a set of 511 genes that have a strong genomic domestication footprint. On the other hand, using allele-specific expression and network analyses from one domesticated and one wild chili pepper accession, as well as their cross, at 40 days after anthesis (DAA), the authors of [ 41 ] proposed that gene expression differences associated with the cultivated form could be explained by cis -regulatory hubs acting through trans -regulatory cascades.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years transcriptomics has been used to study the effect of domestication on a wide range of species including the major cereals rice [47,48], maize [49,50], wheat (Triticum aestivum) [51], and barley [52], as well as cotton (Gossypium hirsutum) [53], tomato [54,55], eggplant (Solanum melongena) [56,57], peppers [58], sunflower (Helianthus annuus) [59], common bean (Phaseolus vulgaris) [60], curcubita [61], and a range of more other crops including chickpea (Cicer arietinum) [62], lupin (Lupinus albus) [63], pistachio (Pistacia vera) [64], spinach (Spinacia oleracea) [65], lettuce (Lactuca sativa) [66], and jujube (Ziziphus jujube) [67]. A common theme that emerges from these studies is that domestication is associated with a large reduction in allelic diversity, with estimates suggesting that our current crops contain on average only 6% of the allelic diversity present in wild species gene pools [68].…”
Section: Transcriptomics-based Assessment Of the Effects Of Domesticationmentioning
confidence: 99%
“…Hybrid studies have been performed between maize and teosinte, suggesting potential selection on cis regulatory elements associated with changes in ear tissue and previously reported candidate genes (Lemmon et al, 2014). Another hybrid study in Capsicum annuum using network analyses revealed that loss of function in cis regulatory sequences lead to transcriptional changes in trans elements that are associated with fruit morphology (Díaz-Valenzuela et al, 2020).…”
Section: Successful Examples Of Rna-seq Experiments To Understand Dommentioning
confidence: 92%